2015
DOI: 10.1039/c4ta07213h
|View full text |Cite
|
Sign up to set email alerts
|

Incorporation of Ag nanowires in CuWO4 for improved visible light-induced photoanode performance

Abstract: We report the sol-gel synthesis of a CuWO 4 (E g $ 2.0-2.15 eV) thin film loaded with Ag nanowires. The incorporation of Ag nanowires into the semiconductor matrix significantly improves the performance of CuWO 4 as a photoanode for use in photochemical water splitting (PEC). Here, we have developed a planar electrode to test the photoactivity of the catalyst using standard electrochemical procedures under simulated solar light. The sol-gel synthesis of CuWO 4 is modified such that we add Ag nanowires during s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

2
44
0

Year Published

2017
2017
2022
2022

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 56 publications
(46 citation statements)
references
References 41 publications
2
44
0
Order By: Relevance
“…Particularly, the presence of Cu2O and CuO, enhance the photocatalytic activity and photocurrent generation. By comparing with earlier report, the nobel‐metal (Ag) incorporated CuWO 4 showed the photocurrent 1.5 mA/cm 2 at 1.23 V vs NHE. In the present study, the Cu 2 O and CuO incorporated CuWO 4 showed high photocurrent 3.5 mA/cm 2 at 1.23 V vs RHE.…”
Section: Resultssupporting
confidence: 51%
See 3 more Smart Citations
“…Particularly, the presence of Cu2O and CuO, enhance the photocatalytic activity and photocurrent generation. By comparing with earlier report, the nobel‐metal (Ag) incorporated CuWO 4 showed the photocurrent 1.5 mA/cm 2 at 1.23 V vs NHE. In the present study, the Cu 2 O and CuO incorporated CuWO 4 showed high photocurrent 3.5 mA/cm 2 at 1.23 V vs RHE.…”
Section: Resultssupporting
confidence: 51%
“…The first order derivative cut off wavelength is observed at 720 nm for normalCnormalunormalWnormalO4 particles. Its band gap value deduced using the formula Eg (eV)=1240 /λ (nm) and found to be 1.78 eV (Figure S9), which is smaller than the reported Eg of normalCnormalunormalWnormalO4 (2.1 ‐ 2.3 eV) ,…”
Section: Resultsmentioning
confidence: 66%
See 2 more Smart Citations
“…Please do not adjust margins Please do not adjust margins (3dx 2 -y 2 )) negatively affect the overall water splitting efficiency [13][14][15]18]. Generally, for tungstate-based semiconductors, various strategies have been reported to improve their usability [19][20][21][22][23][24][25][26][27][28][29].…”
Section: Introductionmentioning
confidence: 99%